Jurnal Pengabdian Masyarakat: Pemberdayaan Ibu PKK di Kelurahan Jatirejo - Emmywati, Emmywati; Suprihandari, Miya Dewi; Hanifah (PUTRA JAWA PUBLISHER, 2024)
Empowering PKK (Family Welfare Empowerment) mothers plays an important role in local community development, especially in Jatirejo Village. This article describes the results of a community service program which aims to increase the capacity of PKK mothers through various training and direct activities. The program's main focus is on improving economic skills, health knowledge, and social participation. The methodology used includes small business skills training, health workshops, and digital literacy activities. The results of the program show a significant increase in the abilities and self-confidence of PKK mothers, which ultimately has a positive impact on the welfare of the community in Jatirejo Village. This program also identifies the challenges faced and offers recommendations for the sustainability of empowerment initiatives in the future.